Adrenal insufficiency following nivolumab therapy in patients with recurrent or metastatic head and neck cancer. Issue 2 (April 2020) - Kagoshima, Hiroki; Hori, Ryusuke; Kojima, Tsuyoshi; Okanoue, Yusuke; Fujimura, Shintaro; Taguchi, Atsushi; Shoji, Kazuhiko
Abstract: Nivolumab, an anti-programmed cell death-1 monoclonal antibody, is currently used to treat many types of advanced cancers including recurrent and metastatic head and neck cancer. However, there are increasing reports concerning immune-related adverse events related to nivolumab therapy. Here, we report three patients who presented with adrenal insufficiency following nivolumab therapy. Two were diagnosed as having isolated adrenocorticotropic hormone (ACTH) deficiency and one was diagnosed as having primary adrenal insufficiency. All three patients complained of progressive fatigue and appetite loss, so we measured their blood cortisol and ACTH levels and diagnosed them as having adrenal deficiency. Treatment with nivolumab was discontinued for all three patients, and replacement therapy using hydrocortisone was successful after a few days in all cases. Two patients subsequently resumed nivolumab therapy because their general condition had improved. Complaints of fatigue and appetite loss during cancer treatment are common and tend to be regarded as unimportant. Although adrenal insufficiency due to nivolumab is relatively rare, complaints of these symptoms could lead to the detection of adrenal insufficiency at an early stage. The present report highlights the importance of the early recognition of adrenal insufficiency.